Браслети з зооморфними закінченнями (за матеріалами розкопок могильника Острів 2017—2020 рр.) - Дяченко, Д.Г. (Археологія і давня історія України, 2021)
Стаття присвячена браслетам зі зооморфними
закінченнями, виявленим на західнобалтському
некрополі Острів у 2017—2020 рр. Розглядаються
типи прикрас, стиль, історія досліджень. The bracelets with zoomorphic terminals are analyzed
in the paper. They were found in the West Baltic
Ostriv burial ground in 2017—2020. The work shows
types of jewelry, their style, and history of research.
The assemblage of 15 samples has dissimilar configuration.
Furthermore, 10 of them were found in female
burials, 2 — male burials, 1 — archaeological level
and 2 are accidental finds. These bracelets have arcuate
shape, terminals with stylized reptile heads. Their
surface is decorated with a geometric ornament that
emphasizes the overall zoomorphic motif and mimics
the reptile in motion.
According to L. Vaitkunskene’s typology, the collection
of Baltic zoomorphic bracelets from the Ostriv
burial ground can have four types.
Because of this features, such as overall tendency developing
shapes of products, specifics of application of
geometric ornament (advantage of combination of lines
and circles on the surface of bracelets from Curonian
area; dominance of geometric figures in ornamentation
of Daugava Livonians, Selonians and Latgalians), and
their chronology, the collection of Baltic zoomorphic
bracelets from the Ostriv burial ground are similar to
the West Baltic tribe of Curonians, the antiquities of
the end of X — first half of XI century.
The author assumes that some of bracelets from the
Ostriv burial ground were made directly in Porossya.
He examined the samples of ones in full detail and
found out that different pieces of bracelets have similar
features. Foremost, they are the design of the stylized
eyes of animal-headed terminals and the similarity of
geometric plots, which, in general, do not have a bright
variety and could be made by a certain master.
Summing up, further systematic research of burial
ground Ostriv and the open-air settlement in the tract
of Stari Sukholisy allows to growth available sources.
It will promote a deeper understanding of various facets
of the material culture of the Baltic immigrant community.